2015
DOI: 10.1108/ecam-01-2014-0013
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between top managers’ leadership and infrastructure sustainability

Abstract: Purpose -Top managers who possess outstanding leadership competence make significant contributions toward achieving project success. The relationship between the top managers' leadership and infrastructure sustainability (IS), one of the most important project success criteria, is empirically researched in this study. The purpose of this paper is to explore relationships between top managers' leadership competence of intellectual competence (IQ), managerial competence (MQ), and emotional and social competence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…The AMOS20.0 was used to fit the model, and then we found that several main goodness-of-fit (GOF) measures did not meet the recommended levels which have been suggested in previous studies [88,89]. Thus, the initial SEM model needed to be refined and optimized.…”
Section: Model Testmentioning
confidence: 98%
“…The AMOS20.0 was used to fit the model, and then we found that several main goodness-of-fit (GOF) measures did not meet the recommended levels which have been suggested in previous studies [88,89]. Thus, the initial SEM model needed to be refined and optimized.…”
Section: Model Testmentioning
confidence: 98%
“…As mentioned in the literature review, sustainable building project is a new type of building and BIM technology has not been used for a long time around the world. As such, there are few experts who know how to apply the two technologies [55]. This makes the government and construction companies particularly critical in developing cross-disciplinary talent.…”
Section: Discussionmentioning
confidence: 99%
“…Goodness-of-fit (GOF) measures are an effective way to improve the fitness of an initial model [55]. After adding covariance error paths among observed variables or latent variables, the model showed a good fit and all of the GOF measures met recommended levels.…”
Section: Refining the Modelmentioning
confidence: 99%
“…The RMSEA value of 0.02, being less than 0.5, indicates that the final refined model is accepted with a very high level of confidence. Additionally, all of the relative indexes of NFI, RFI, IFI, TLI, and CFI are above 0.9, providing strong evidence for the acceptable fit between the measurement model and the data [56,[58][59][60]. Although the correlation setup in this study is according to the suggestions by the MI, the modifications are considered as theoretically and practically plausible.…”
Section: Gof Measuresmentioning
confidence: 99%
“…[56,[58][59][60] As shown in Table 3, some main goodness-of-fit (GOF) measures, such as χ 2 /degrees of freedom (2.31 > 2), adjusted goodness-of-fit index (AGFI 0.807 < 0.9), and root mean square error of approximation (RMSEA 0.073 > 0.05), were not achieved. Therefore, the SEM needed to be simplified and refined to satisfy both the theoretical expectations and the GOF measures.…”
Section: Gof Measuresmentioning
confidence: 99%